Effect of whey protein concentrate on the quality of smoked chicken sausages from broiler spent hens - Rao, K H; Anjaneyulu, A S R; Singh, R R B; Dubey, P C; Yadav, P L (The Indian Journal of Animal Sciences, 2012)
Quality of smoked chicken sausages formulated with broiler spent hen meat and edible byproducts in natural proportion and different levels of whey protein concentrate (WPC) was examined. The edible components available for product processing were 67% lean meat, 11.4% fat, 19% skin and 2.6% gizzard and heart. Addition of WPC at 1.5% significantly (P<0.05) improved emulsion stability and pH of the batter and the sausage yield. Frying loss and shear force values of the experimental samples decreased significantly (P<0.01) with increasing levels of WPC. Moisture and protein contents of sausages with WPE were higher than those of the control. Incorporation of WPC up to 2.5% significantly improved flavour, juiciness, texture and overall palatability of the product. Use of WPC up to 2.5% improved the quality of smoked chicken sausages and facilitated the utilization of all the lean meat and edible by products in natural proportions from broiler spent hens for sausage production.